Front Cover: Density Functional Theory Study of Reaction Equilibria in Signal Amplification by Reversible Exchange (ChemPhysChem 19/2021). Issue 19 (7th October 2021) - Lin, Kailai; TomHon, Patrick; Lehmkuhl, Sören; Laasner, Raul; Theis, Thomas; Blum, Volker
Abstract : The Front Cover shows the reaction network of Signal Amplification by Reversible Exchange (SABRE), elucidated by density functional theory (DFT). More information can be found in the Article by T. Theis, V. Blum, and co‐workers .